2001
DOI: 10.1002/qj.49712757202
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear dynamical perspective on model error: A proposal for non‐local stochastic‐dynamic parametrization in weather and climate prediction models

Abstract: S u MMARYConventional parametrization schemes in weather and climate prediction models describe the effects of subgrid-scale processes by deterministic bulk formulae which depend on local resolved-scale variables and a number of adjustable parameters. Despite the unquestionable success of such models for weather and climate prediction, it is impossible to justify the use of such formulae from first principles. Using low-order dynamicalsystems models, and elementary results from dynamical-systems and turbulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
429
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(437 citation statements)
references
References 69 publications
8
429
0
Order By: Relevance
“…The basic results are that one can approximately treat the effect of fast modes on the slow dynamics by adding suitably defined deterministic and stochastic (with white spectrum) forcing terms in the evolution equations of the slow variables [327,328]. While the use of deterministic, mean field parametrizations for processes like convection, which cannot yet be captured by the relatively coarse grids of most weather and climate models is a standard practise in geophysical fluid dynamical modelling [329,330,24], currently weather and climate modelling centres are moving in the direction of introducing stochastic parametrizations [331,332], as mounting evidences suggest that they are more effective than usual deterministic methods [333,334]. It is indeed not clear to what extent such methods, which aim at being able to describe the typical behaviour of the slow variables, perform in terms of providing a good representation of extreme events.…”
Section: Extremes Coarse Graining and Parametrizationsmentioning
confidence: 99%
“…The basic results are that one can approximately treat the effect of fast modes on the slow dynamics by adding suitably defined deterministic and stochastic (with white spectrum) forcing terms in the evolution equations of the slow variables [327,328]. While the use of deterministic, mean field parametrizations for processes like convection, which cannot yet be captured by the relatively coarse grids of most weather and climate models is a standard practise in geophysical fluid dynamical modelling [329,330,24], currently weather and climate modelling centres are moving in the direction of introducing stochastic parametrizations [331,332], as mounting evidences suggest that they are more effective than usual deterministic methods [333,334]. It is indeed not clear to what extent such methods, which aim at being able to describe the typical behaviour of the slow variables, perform in terms of providing a good representation of extreme events.…”
Section: Extremes Coarse Graining and Parametrizationsmentioning
confidence: 99%
“…This may be similar to the upscale energy cascades that are simulated by some current stochastic parametrizations (Palmer, 2001;Shutts, 2005). An average correlation of less than −0.5 was found between the value of adv in a T 95 grid box and the subgrid-scale interquartile range of the T 799 temperature tendencies contained in that grid box.…”
Section: The Relative Roles Of the Two Componentsmentioning
confidence: 53%
“…This is likely to be because these phenomena depend on small-scale organization, which simply is not resolved, nor properly represented by existing deterministic parametrizations. Introducing structured but random noise has the potential to help NWP models evolve more realistically (Palmer, 2001). Williams et al (2003) showed experimentally and later in a model (Williams et al, 2004) that adding noise can cause a rotating annulus experiment to transition from wave number two to wave number one.…”
Section: Introductionmentioning
confidence: 99%
“…After all, stochastic processes are the macroscopic manifestation of unresolved nonlinear interactions. As stochastic parameterizations become popular (e.g., Buizza et al, 1999;Palmer, 2001), the accuracy of probabilistic forecasts will increasingly depend on how appropriate the stochastic representation is to the physical process it is meant to represent, despite the fact that ensemble weather forecasting does take an average of the ensemble members to improve the forecast. The dynamical form the CLT (Papanicolaou and Kohler, 1974;Sardeshmukh et al, 2001) offers some guidance for doing this.…”
Section: Summary and Discussionmentioning
confidence: 99%